Uticaj pola na dijagnostički i prognostički značaj dobutaminskog stres-ehokardiografskog testa na ishemiju - Trninić, Dijana; Pejičić Popović, Snježana; Jovanić, Jelena; Marjanović, Miron; Kovačević, Siniša; Dobrijević, Neno; Lazarević, Aleksandar Milan (Vojnosanitetski pregled, 2024)
Background/Aim. Cardiovascular diseases are the most common cause of mortality and morbidity worldwide, with the highest incidence in low-middle-income countries. Dobutamine stress echocardiography (DSE) plays a significant role in diagnosing coronary artery disease. The aim of the study was to examine the influence of gender on the accuracy of DSE and on the prognostic significance of the left ventricular wall motion score index (WMSI) as a parameter of DSE for adverse cardiovascular events (ACEs). Methods. The prospective, observational study conducted at the Clinic for Cardiovascular Diseases of the University Clinical Center of the Republic of Srpska, Bosnia and Herzegovina, included 143 patients who, due to suspicion of coronary disease, underwent a DSE from January 1, 2021, until February 1, 2022. ACEs that we observed one year after DSE were: unstable angina, acute myocardial infarction, percutaneous coronary intervention, in-stent restenosis, aortocoronary bypass, heart failure, and death. Results. A positive DSE was more common in men (45%) compared to women (25%), which was statistically significant (p < 0.05). The sensitivity of the test in men was 96.0%, and the specificity was 93.9%. In women, the sensitivity was 86.7%, and specificity was also 86.7%. ACEs were more frequent in men (43%) than in women (19%), which was statistically significant (p < 0.01). In men, WMSI had a sensitivity of 96.0% and a specificity of 82.4%. In women, WMSI had a sensitivity of 93.3% and a specificity of 90.6% in predicting ACEs. Conclusion. Our results confirmed the influence of gender on the accuracy of DSE in diagnosing coronary artery disease. WMSI as a parameter of DSE was identified as a significant prognostic factor for ACEs in both sexes, with the sensitivity being higher in men and specificity in women.